2019
DOI: 10.1177/1461444819858081
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with and reflecting on the materiality of digital media technologies: Repair and fair production

Abstract: How do people think about and engage with the materiality of digital media technologies and thereby try to transform the devices and society? The article discusses this question by presenting the results of two qualitative studies in which people reflect on and engage with the materiality of media technologies. In the first case, the repairing of media devices in Repair Cafés was analyzed, in the second, the focus was on the production and appropriation of the Fairphone, a smartphone which should be produced u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 30 publications
(36 reference statements)
0
33
0
Order By: Relevance
“…However, five articles also highlighted the more social aspects of repair café set-ups, including the fact that the materials, tools and know-how to fix broken consumer products are being provided to the visitors [46]. Furthermore, repair cafés constitute places where visitors can bring their broken items and attend free of charge [42,[46][47][48][49], thus touching upon the more social aspects of the set-up, in particular the inclusion of people with a low income.…”
Section: Set-up and Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…However, five articles also highlighted the more social aspects of repair café set-ups, including the fact that the materials, tools and know-how to fix broken consumer products are being provided to the visitors [46]. Furthermore, repair cafés constitute places where visitors can bring their broken items and attend free of charge [42,[46][47][48][49], thus touching upon the more social aspects of the set-up, in particular the inclusion of people with a low income.…”
Section: Set-up and Proceduresmentioning
confidence: 99%
“…Repair cafés have a general focus on electronic products [30,50,51], and receive and recover broken [42] or defective everyday objects [9,47,52]. One article indicated that the products brought for repair include items that are 'highly valued' [46] (p. 934).…”
Section: Products and Typesmentioning
confidence: 99%
See 3 more Smart Citations